Cigarette smoking, birthweight and osteoporosis in adulthood: results from the hertfordshire cohort study. - Moinuddin, M; Jameson, K; Syddall, H; Sayer, A; Martin, H; Robinson, S; Cooper, C; Dennison, E (2008)
We looked for interaction between early environment and adult lifestyle in determination of bone mineral content (BMC) and bone mineral density (BMD) among 498 men and 468 women for whom birth records were available. Participants completed a health questionnaire, and bone densitometry (DXA) of the lumbar spine and femoral neck performed.We found no relationships between cigarette and alcohol consumption, physical activity and either BMC or BMD after adjustment for age, body mass index, dietary calcium, social class, HRT use and years since menopause. However, male current smokers in the lowest third of birth weight had lower femoral neck BMD than ex- or never smokers from the lowest birth weight third (p value for interaction term = 0.04). Similar trends were seen with femoral neck BMC and lumber spine BMC.Individuals of lower birth weight may be particularly vulnerable to the effects of bone noxious stimuli such as cigarette smoking.